Pengaruh Pemikiran Muhammad Abdul Karim Al-Syahrastani Terhadap Perkembangan Studi Agama-Agama Di Indonesia (Kajian Kitab Al-Milal Wa Al-Nihal) - Ruslan, Idrus; Rosana, Ellya (AL-ADYAN, 2020)
This article focuses on discussing the influence of Al-Syahrastani’s thoughts on the study of religions in Indonesia. The field of study of religions, which originally is called comparative study of religions, is a branch discipline of religious sciences, century-long established in the world, including in Indonesia. In his book al-Milal wa al-Nihal, Syahrastani explains a variety of religious communities, such as the Stoicism, the materialists, atheist philosophers, the Shabi’un, and many others including the ahl al-kitab (communities of the book). This study is of a literary research, and basses its analysis on both primary and secondary sources. Results of this study point to the influences of Syharastani’s thoughts on the development of study of religions in Indonesia. While these influences are indirect in nature, a large number of Muslim and non-Muslim scholars in Indonesia has referred to Syahrastani’s thoughts. Even the publication of the Indonesian translation of Syahrastani’s al-Milal wa al-Nihal, has enabled students of the department of study of religions in many Indonesian Islamic universities to learn various category and types of religious communities as solicited by Syahrastani.